High‐resolution imaging and monitoring of animal tunnels using 3D ground‐penetrating radar. Issue 3 (5th April 2019) - Allroggen, Niklas; Booth, Adam D.; Baker, Sandra E.; Ellwood, Stephen A.; Tronicke, Jens
ABSTRACT: Ground‐penetrating radar is widely used to provide highly resolved images of subsurface sedimentary structures, with implications for processes active in the vadose zone. Frequently overlooked among these structures are tunnels excavated by fossorial animals (e.g., moles). We present two repeated ground‐penetrating radar surveys performed a year apart in 2016 and 2017. Careful three‐dimensional data processing reveals, in each data set, a pattern of elongated structures that are interpreted as a subsurface mole tunnel network. Our data demonstrate the ability of three‐dimensional ground‐penetrating radar imaging to non‐invasively delineate the small animal tunnels (∼5 cm diameter) at a higher spatial and geolocation resolution than has previously been achieved. In turn, this makes repeated surveys and, therefore, long‐term monitoring possible. Our results offer valuable insight into the understanding of the near‐surface and showcase a potential new application for a geophysical method as well as a non‐invasive method of ecological surveying.